The alphabet from A to Y with bonus letter, Z! - Martin, Steve, 1945-; Chast, Roz (New York : Flying Dolphin Press, 2007)
Presents a rhyming couplet featuring each letter of the alphabet, with such characters as David the dog-faced boy, who dons a derby despite being dirty, and Victor, whose frequent victories have made him vainglorious.
Keywords: Alphabet books; Behavior -- Fiction; Alphabet; Humorous stories; Stories in rhyme; Picture books for children